Practice Rehearsal Pairs dalam Pembelajaran Tari Dana-Dana Kreasi pada Siswa di SMP Negeri 1 Botumoito - Djakatara, Rifka (Ideas: Jurnal Pendidikan, Sosial dan Budaya, 2024)
21st century learning experiences obstacles in learning dance where students are not yet familiar with dance movement motifs and creations. The aim of the research is to describe the Dana Kreation breast dance lesson using the pair training method, namely helping students to demonstrate the Dana-danaKreation breast dance according to the supporting elements of the dance. The results of this research are: students are enthusiastic about paying attention to the model to demonstrate dance movements in front of the class and it is hoped that students will be able to demonstrate dance movement motifs and creations according to the dance music. This learning evaluation is an effort to apply the pair training method in learning the dana-dana Kreation dance for students at SMP Negeri 1 Botumoito, provide the best results